Training on Utilizing Pipe Waste Become an Useful Handicrafts at MA Syamsul Arifin Students Kraton Pasuruan: Pelatihan Pemanfaatan Limbah Paralon Menjadi Kerajinan Tangan Bagi Siswa MA Syamsul Arifin Kraton Pasuruan - Hasan Syaiful Rizal; M. Mustofa (LPPM Universitas Yudharta Pasuruan, 2022)
This community service focuses on equipping assisted subjects with knowledge about the use of PVC pipe waste in the environment. This service program is an actualization of the collaboration that has existed between Yudharta University Pasuruan and Madrasah Aliyah Syamsul Arifin Kraton Pasuruan. This mentoring program uses a service learning approach through three stages including the preparation, service, and reflection stages. The impact of this change in service includes students being able to understand various types of waste and their impact on the environment, being able to make handicrafts using used plastic pipe waste materials, and being able to understand marketing strategies for handicraft products by utilizing existing facilities in the surrounding environment. This service activity is expected to be a pioneer of collaboration between institutions, especially in increasing the creativity and independence of students in various schools in the Pasuruan Regency.